Dendrimers in combination with natural products and analogues as anti-cancer agents. (20th November 2017) - Mignani, Serge; Rodrigues, João; Tomas, Helena; Zablocka, Maria; Shi, Xiangyang; Caminade, Anne-Marie; Majoral, Jean-Pierre
Abstract : Overview of the use of dendrimers in combination with encapsulated and conjugated natural products and analogues as anti-cancer agents. Abstract : For the first time, an overview of dendrimers in combination with natural products and analogues as anti-cancer agents is presented. This reflects the development of drug delivery systems, such as dendrimers, to tackle cancers. The most significant advantages of using dendrimers in nanomedicine are their high biocompatibility, good water solubility, and their entry – with or without encapsulated, complexed or conjugated drugs – through an endocytosis process. This strategy has accelerated over the years in order to develop nanosystems as nanocarriers, to decrease the intrinsic toxicity of anti-cancer agents, to decrease the drug side effects, to increase the efficacy of the treatment, and consequently to improve patient compliance.